The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/07435800.2017.1292527
|View full text |Cite
|
Sign up to set email alerts
|

Changes of bone mineral density and serum pentosidine during a 27-month follow-up of monthly minodronate in osteoporotic patients

Abstract: Monthly minodronate treatment increased BMDs in newly treated patients over 27 months. Serum Pen increased with M-MIN therapy, possibly indicating prolonged bone turnover. The initial 9-month changes in serum P1NP predicted the 27-month changes in hip BMDs when M-MIN replaced alendronate or risedronate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Our study showed that estimated glomerular filtration rates (e-GFRs) were significantly decreased during the 27-month period of monthly minodronate therapy in female patients with osteoporosis. 38 However, the rate of decrease was almost the same as was found in the placebo group in the Health Outcomes and Reduced Incidence with Zoledronic Acid Once Yearly (HORIZON) Recurrent Fracture Trial, wherein zoledronate was administered intravenously once a year for 3 years after hip fracture. 46 It could indicate that the decrease in e-GFR observed during monthly minodronate therapy in our study was probably due to aging.…”
Section: Safetymentioning
confidence: 71%
See 1 more Smart Citation
“…Our study showed that estimated glomerular filtration rates (e-GFRs) were significantly decreased during the 27-month period of monthly minodronate therapy in female patients with osteoporosis. 38 However, the rate of decrease was almost the same as was found in the placebo group in the Health Outcomes and Reduced Incidence with Zoledronic Acid Once Yearly (HORIZON) Recurrent Fracture Trial, wherein zoledronate was administered intravenously once a year for 3 years after hip fracture. 46 It could indicate that the decrease in e-GFR observed during monthly minodronate therapy in our study was probably due to aging.…”
Section: Safetymentioning
confidence: 71%
“… 37 According to our study, a significant increase in the lumbar spine BMD at 27 months of monthly minodronate therapy, compared with the baseline value in the switch group, in 47 female patients with osteoporosis was observed. 38 Because of the stronger efficacy for the inhibition of bone resorption of minodronate than that of alendronate or risedronate, more BMD gain is expected when alendronate or risedronate is replaced by minodronate. However, when enough remodeling space in the bone is not available for minodronate to exert its action because of prior bisphosphonate therapy, the BMD may not increase.…”
Section: Other Clinical Studies On Minodronatementioning
confidence: 99%
“… 2008 ; Ohishi et al. 2017 ). In this current study, 7 weeks AU treatment significantly increased the serum concentrations of P1NP in OP mice relative to control mice, which preliminarily proves that AU slowed the development of OP by increasing bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…If a metal implant was inserted on the left side, the BMD of the right hip was measured. The coefficient of variation (CV) for lumbar, femoral neck, and total hip BMD were described in our previous paper [ 16 ]. Serum type 1 procollagen N-terminal propeptide (S–P1NP), urinary N-terminal type I collagen telopeptide (U-NTX), serum total homocysteine (S-Hcy), and cystatin C levels were measured along with routine laboratory examinations.…”
Section: Methodsmentioning
confidence: 99%
“…P-values < 0.05 were defined as statistically significant. The a priori required sample size was calculated using the G∗Power 3.1.9.3 statistical power analysis software program by comparing our previous data on changes in eGFRcr in women with osteoporosis during 27-month minodronate therapy [ 16 ] with annual health check-up data of healthy individuals attending our hospital. The mean changes in eGFRcr during minodronate therapy in 99 postmenopausal women aged 43–93 years (average, 74.5 years) for 27 months was −8.5% with a standard deviation of 11.0%.…”
Section: Methodsmentioning
confidence: 99%